Assessment of functional and pasting properties of fresh orange maize hybrids and open-pollinated varieties as influenced by genotype, harvesting time, and growing location - Alamu, Emmanuel Oladeji; Maziya-Dixon, Busie; Menkir, A.; Adesokan, Michael; Olaofe, O. (Frontiers Media, 2021)
The study evaluates the effects of genotype, maturity, and growing location on the functional and pasting properties of freshly harvested orange maize hybrids and open-pollinated varieties (OPVs). Eight fresh orange maize hybrid and eight fresh maize OPV, including the control, were harvested at three stages: 20, 27, and 34 days after planting (DAP). The freshly harvested maize samples were lyophilized and characterized for the pasting and functional properties using standard laboratory methods. The peak viscosity, final viscosity, and swelling power of the OPVs increased between 20 and 27 DAP. Additionally, the water absorption capacity increased between 20 and 27 DAP for the maize hybrids, with a decreasing trend between 27 and 34 DAP. However, genotypes 2, from the orange maize hybrid, and 5, amongst the OPV, were outstanding with the highest peak viscosities, indicating good final product quality. The combined ANOVA for the fresh orange maize hybrid and OPV showed a highly significant effect (p ≤ 0.01 and p ≤ 0.001) for the maturity and location on the pasting and functional properties except for the pasting temperature, final viscosity, and pasting time which showed no significant effect. In contrast, the location by genotypes by maturity interactions had no significant effects on the pasting and functional properties of the fresh maize hybrid and the orange OPV except only for the setback, which was highly significant at p ≤ 0.001. Nutritionists, food scientists, and maize breeders could use the information from this study to select the best maize genotypes at the appropriate harvesting period suitable for the production of the preferred maize-based products of consumers.